Pros and cons of a bone-conduction device implanted in the worse hearing ear of patients with asymmetric hearing loss - Kurihara, Sho; Ganaha, Akira; Nakamura, Takeshi; Kubuki, Kan; Saruwatari, Emi; Matsui, Koudai; Takahashi, Kuniyuki; Tono, Tetsuya (Frontiers in Audiology and Otology, 2024)
Purpose Bone-conduction devices can be considered a viable treatment option for patients experiencing asymmetric hearing loss (AHL), especially those with severe to profound hearing loss (HL) present in one ear. However, there are only a few reports on the effects of bone-anchored hearing aids (BAHAs) on patients with AHL. This retrospective study analyzed in detail the effects of BAHA on softer sounds than other hearing aids and identified situations in which BAHA had a negative effect. Methods Patients with AHL, characterized by severe to profound hearing loss in one ear with a difference of ≥45 dB from that of the contralateral ear, underwent BAHA implantation in the ear with worse hearing. The BAHA effects were evaluated by assessing the word recognition score (WRS) and speech reception threshold (SRT) using the Japanese Oldenburg Sentence Test for various signal settings and noise directions. For a subjective analysis, the Speech, Spatial and Qualities of Hearing Scale (SSQ12) score was determined. Results Thirteen patients who underwent BAHA implantation at the Miyazaki University Hospital between 2007 and 2021 were included. The BAHA demonstrated a significant improvement in the WRS from 40 to 70 dB sound pressure levels. Although the SRT showed significant improvement in noisy environments when speech was presented to the BAHA-wearing side, it worsened significantly when noise was presented to this side. In the survey of subjective hearing ability, both the total and subscale SSQ12 scores improved significantly after wearing the BAHA. Conclusion This study identified scenarios in which BAHAs were beneficial and detrimental to individuals with AHL. Generally used audiological tests, such as the WRS with fixed sound pressure, may underestimate the effectiveness of BAHAs for softer sounds. In addition, depending on the direction of the noise, BAHAs may have adverse effects. These results could help patients comprehend the potential benefits and limitations of bone-conduction devices for their hearing.